Pressures and their Relation to the Psychological Hardiness among Breast Cancer Patients - Al-Masri, Anas Ramadan (Journal of Educational and Psychological Sciences, 2020)
The current study aims at recognizing the relationship between the health,family,social,economic and psychological pressures and their relation to psychological hardiness among breast cancer patients.The researcher follows descriptive and explanatory approaches to explain this relationship.The research sample consists of 150 women affected by breast cancer;and researcher used the scale of breast cancer patients’ pressures(prepared by Hijazi,2012), as well as the scale of psychological hardiness (prepared by Mukhaimer,1997).Results indicated having a negative correlation between the overall rigidity aspect and the health,family,social,economic and psychological pressures. Results indicated that women affected by breast cancer have psychological hardiness, having a negative correlation between the aspects of commitment and control, and the health, family, social, economic, psychological, having a correlation between the aspect of control and the health and economic pressures, having a negative correlation between the aspect of the challenge and the family, social, economic, psychological, having differences of statistical significance in control referring to the marital status variable for the married women and having differences of statistical significance in control, challenge, commitment referring to the number of children variable.